Pelaksanaan Kewajiban Majelis Pengawas Daerah Gabungan Kabupaten Pengandaran, Kota Banjar, Kabupaten Ciamis Dalam Pemeriksaan Laporan Pengaduan Masyarakat - Merdekawati, Melati (Recital Review, 2023)
This study aims to find out and analyze the reasons why the Joint Regional Supervisory Council does not carry out its obligations in examining community complaint reports and the next purpose is to find out and analyze the legal consequences of the Joint Regional Supervisory Council that does not carry out its obligations in examining community complaint reports. This type of research uses empirical normative research, while it is descriptive in nature. The type of research data is primary data and secondary data. Primary data obtained through direct field research, namely respondents and resource people. Secondary data is regarding on the collection of materials related to the topic of research. Secondary data consist of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis conducted by qualitative manner. The conclusion of the research shows first, the Combined MPD of Pangandaran Regency, Banjar City, Ciamis Regency had carried out its obligations in examining community complaint reports but did not complete the reason for the Combined MPD of Pangandaran Regency, Banjar City, Ciamis Regency for humanitarian reasons because of the conditions experienced by the Reported. Second, the legal consequences for the Joint MPD that does not carry out its obligations in examining public complaint reports are not clearly regulated in law, it’s just that referring to the provisions of Article 17 of Permenkumham Number 16 of 2021, this action is included in violating the oath/promise of office which provides legal consequences for imposing sanctions in the form of dishonorable dismissal based on Article 18 Paragraph (3) letter f of Permenkumham Number 16 of 2021.